Sing A Song for Home: How Displaced Iranian Song-Writers in LA Conceive of Home and Homeland - Pouya Morshedi; Lisa-Jo K. van den Scott (Qualitative Sociology Review)
We ask how being apart from home impacts the very definition of home. We conducted a content analysis of songs produced by Iranians who have left their first “home” in Iran and resettled in Los Angeles. Our findings suggest that distance from one’s home expands the definition and image of home from a structure where one dwells and calls home, to an imagined community at the personal (home family), local (hometown), and regional (homeland) levels. The 1979 revolution in Iran caused many people, including singers and songwriters, to immigrate. Many of them moved to Europe and North America. We analyzed songs from 1979 to 1999, produced in Los Angeles, as the heart of Iranian pop music after the revolution, focusing on the concept of “home.” Four main themes emerged: the “body of the home,” which includes windows, niches, and gardens; “homeland as home;” “home and family;” “home as a heaven to remember and a haven for return,” which involves home as a place for making memories and recalling them and home as a retreat. We explain how these themes are related to Iran’s situation post-revolution, the image of the Iranian home, and the singers’ situation in Los Angeles after the revolution. The most significant finding is the relationship between home and homeland. Songs use home as a metaphor for the homeland, even when describing the body of the home. The sadness about the destroyed home, hope to return to home, and the tendency to come back to their mother (or motherland) point to the singers’ emotions about their homeland. The distance from home has changed the conceptualization of “home.” The borders of home are not around the songwriters’ houses or intimate families anymore, but they are around the homeland.